Advancing towards the integral development of the person: Approach to the concept of spiritual intelligence - Alarcón Orozco, Elena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
In the present work, an approach to the concept of spiritual intelligence is exposed as part of the bio-psycho-socio-spiritual reality of the human being, with the aim of generating the need for a spiritual education that completes emotional education and favours integral development of the person, as a fundamental part of the purpose of the educational system.